ANALYSIS ON THE RELATIONSHIP BETWEEN SPATIAL STRUCTURE AND DRILLING SPACE ON THE EXPLORATION OF ALLUVIAL TIN DEPOSIT ONSHORE AND OFFSHORE, MUNTOK AREA, BANGKA BELITUNG ISLAND PROVINCE - FRAMIKA (NIM : 12104032); Dosen Pembimbing : Dr. M. Nur Heriawan, ST., MT., DORES
One of mineral resources in Indonesia, which has a substantial role and influence is Tin (Sn). In order to get maximum benefit from tin mining, it is required an appropriate method from each of the stages of exploration and mining. If the methods of exploration have considered aspects of genesis and spatial aspects, then the resource calculation will be obtained with a good confidence level. This study will analyze relationship between spatial structure that will be seen from the variogram model against grid density of the drilling data for alluvial tin deposit on land and sea, so it is expected can be determined optimum drilling space for alluvial tin deposits on land and at sea. spacing of Exploration drilling at land average is 40 m, while at sea is 100 m. From the results of variogram analysis of onshore drilling is obtained range for the calculated grade tin (TDH) about 80 - 190 m, while thickness about 135 Ã‚Â– 275 m. while the results of variogram analysis of offshore drilling is obtained range for TDH is 365 m, while thickness is 320 m. From the calculation of the value ratio nugget is found that TDH land and sea have low enough ratio nugget that is about 10% and 4%, so the tin grade estimation can be done using Ordinary Kriging (OK). While the value ratio nugget of thickness land and sea have high ratio nugget that is about 54% dan 59%, so thickness estimation can be done using Moving Average (MA). From the comparison between ratio nugget effect and range against space drilling, it can be concluded that drilling exploration for spacing 40 m on land and drilling exploration for spacing 100 m at sea have been quite optimum.